Sleepover zoo - Kearns, Brenda, 1963-; Lowe, Wesley (Richmond Hill, Ont. : Scholastic Canada, 1998)
Leona is the most popular girl in the class,and her house is perfect. What will she think when she sees Toni's crazy house full of animals? A tale of fun, teathers, friendship and a sleepover.
Approved for use in Ontario schools 1998, Grade 4 Language Arts (English)
ALM
CR
Keywords: Language arts; English language -- Study and teaching (Elementary); Readers (Elementary); Young adult fiction -- Study and teaching (Elementary); Friendship -- Juvenile fiction; Animals -- Juvenile fiction; Sleepovers -- Juvenile fiction